An Approach for the Transformation of Human Emotion and Energy-Field using Sound Therapy (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The human emotions are very dynamic in nature, and get transformed from one mood to another rapidly. Emotion detector systems are available to identify the real-time emotions based on various external parameters like face expressions, lip movements, choice of words in speech and so on. Many applications were developed over and over again that are capable of providing solutions based on current emotions of an individual such as mood based music players. The humans are quite intelligent and smart enough to hide their actual emotion and represents themselves as per the environment, therefore they can fool others easily by expressing their fake expressions. The existing systems need high computation power and works upon probabilistic calculus models. On the other side of the coin, human biofield, energy around human body that reflects inner soul, is powerful enough to represent the actual psychology. It provides the visual verification and validation proofs regarding change in emotions. This research article shows a novel approach for determining the real-time human emotions, integrated with biofield analysis to overcome the mentioned issues. An algorithm is capable of expressing the true internal emotions of a person and classify the original and sarcastic emotions.